2021
DOI: 10.1590/1983-40632021v5167131
|View full text |Cite
|
Sign up to set email alerts
|

In vitro growth of Cattleya nobilior Rchb. f.: culture media, sealing systems and irradiance

Abstract: Some factors may influence the in vitro culture of native orchids, especially the culture medium, sealing system and light condition. This study aimed to evaluate the addition of banana pulp and peel in the formulation of culture media, sealing system and irradiance, in the in vitro growth of Cattleya nobilior Rchb. f. A completely randomized design was used in a factorial scheme with five culture media [Murashige & Skoog supplemented or not with banana pulp or peel (100 or 200g L-1)], two light conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, orchids have a long production period, and, for this reason, other methods are applied for its development and conservation. In vitro culture or micropropagation is the most used alternative for orchids propagation (Freitas et al, 2021), being applied in the stages of germination, seedling growth and rooting; especially for commercial species (Arellano et al, 2020;Cardoso et al, 2020). For this purpose, culture media are used, sometimes complemented with organic substances like banana flour, coconut water and others (Salazar & Botello, 2020;Wida & Hariyanto, 2020) or growth regulators (Parthibhan et al, 2015), to provide the physiological stimulus necessary for their development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, orchids have a long production period, and, for this reason, other methods are applied for its development and conservation. In vitro culture or micropropagation is the most used alternative for orchids propagation (Freitas et al, 2021), being applied in the stages of germination, seedling growth and rooting; especially for commercial species (Arellano et al, 2020;Cardoso et al, 2020). For this purpose, culture media are used, sometimes complemented with organic substances like banana flour, coconut water and others (Salazar & Botello, 2020;Wida & Hariyanto, 2020) or growth regulators (Parthibhan et al, 2015), to provide the physiological stimulus necessary for their development.…”
Section: Introductionmentioning
confidence: 99%
“…Both the highest NR and NL occurred when CSS was used since the conditions established by this system are related to plant tillering, which is affected by the greater number of shoots (Ribeiro et al 2019). Freitas et al (2021) observed a similar result for Cattleya nobilior Rchb.f. cultivated in vitro.…”
Section: In Vitro Growth -120 Daysmentioning
confidence: 56%
“…The results found in this study show that the light condition of the cultivation room for Orchidaceae species are, in addition to speciesspecific, also related to the stage of development of the plant. The results found in the literature differ according to the stage of seedlings used (Freitas et al 2021;Sorgato et al 2021a).…”
Section: In Vitro Growth -120 Daysmentioning
confidence: 87%